2021
DOI: 10.1007/s00122-021-03967-z
|View full text |Cite
|
Sign up to set email alerts
|

Wheat genetic loci conferring resistance to stripe rust in the face of genetically diverse races of the fungus Puccinia striiformis f. sp. tritici

Abstract: Key message Analysis of a wheat multi-founder population identified 14 yellow rust resistance QTL. For three of the four most significant QTL, haplotype analysis indicated resistance alleles were rare in European wheat. Abstract Stripe rust, or yellow rust (YR), is a major fungal disease of wheat (Triticum aestivum) caused by Puccinia striiformis Westend f. sp. tritici (Pst). Since 2011, the historically clonal European Pst races have been superseded by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
46
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(56 citation statements)
references
References 88 publications
8
46
2
Order By: Relevance
“…The MAGIC RILs showed phenotypic variation over the full range of the assessment scale (Figure 1c): nearly 70 % of RILs showed little or no infection (GIF = 0) while ~10 % exhibited Pst infection in the majority of the ear (GIF = 3-4) (Supplementary Figure 2). Pearson’s correlation coefficient analysis of the MAGIC glume YR infection data alongside previously reported leaf YR infection data from the same trials (Bouvet et al 2021b) found a positive correlation at both environments, with OSG16 ( R = 0.62, p <2.2E-16) showing a stronger correlation than was observed at NIAB16 ( R = 0.49, p < 2.2E-16) (Figure 2). MAGIC RILs susceptible in the glumes generally also exhibited high leaf susceptibility (leaf infection >60%).…”
Section: Resultssupporting
confidence: 64%
See 4 more Smart Citations
“…The MAGIC RILs showed phenotypic variation over the full range of the assessment scale (Figure 1c): nearly 70 % of RILs showed little or no infection (GIF = 0) while ~10 % exhibited Pst infection in the majority of the ear (GIF = 3-4) (Supplementary Figure 2). Pearson’s correlation coefficient analysis of the MAGIC glume YR infection data alongside previously reported leaf YR infection data from the same trials (Bouvet et al 2021b) found a positive correlation at both environments, with OSG16 ( R = 0.62, p <2.2E-16) showing a stronger correlation than was observed at NIAB16 ( R = 0.49, p < 2.2E-16) (Figure 2). MAGIC RILs susceptible in the glumes generally also exhibited high leaf susceptibility (leaf infection >60%).…”
Section: Resultssupporting
confidence: 64%
“…Statistical analysis of the glume infection phenotypic data using REML showed that the Wald statistic for genotype effect was highly significant (Chi pr <0.001) at both environments (Supplementary Table 3). High genotypic performance is further supported by high broad sense heritability values at NIAB16 ( h 2 = 0.80) and OSG16 ( h 2 = 0.82), mirroring values observed for leaf infection at the same trials ( h 2 = 0.79-0.94) (Bouvet et al 2021b). This evidence points towards stable genotypic performance for glume infection in the MAGIC population at each site.…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations